2010
DOI: 10.1093/ndt/gfq226
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in advanced chronic kidney disease with or without diabetes: midterm effects of the initiation of chronic haemodialysis therapy

Abstract: CKD is associated with worse cardiac autonomic function. Haemodialysis therapy for 3 months improves some indices of HRV, and this effect is more pronounced in non-diabetic subjects. Our findings suggest that the improvement of HRV after the initiation of chronic dialysis therapy can ameliorate clinical outcomes and survival in patients with end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 36 publications
3
61
0
1
Order By: Relevance
“…Post-dialysis systolic blood pressure was lower in the intensive vitamin D group ( p = 0.03), but blood pressure was well controlled in both groups. All measures of HRV were depressed but were similar between groups and comparable to published measures in the ESKD population [3,24,28,30]. …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Post-dialysis systolic blood pressure was lower in the intensive vitamin D group ( p = 0.03), but blood pressure was well controlled in both groups. All measures of HRV were depressed but were similar between groups and comparable to published measures in the ESKD population [3,24,28,30]. …”
Section: Resultssupporting
confidence: 80%
“…Age, sex treatment sequence, prior vitamin D supplementation, baseline calcium, parathyroid hormone, dialysis adequacy (kt/V), and β-blocker medication were tested as potential effect modifiers within the model, recognizing that the ability to detect significance was limited by sample size. Subgroup analyses were conducted for subjects with diabetes mellitus [28] and subjects on nocturnal hemodialysis [29]. Missing HRV values were imputed utilizing an expectation–maximization (EM) technique.…”
Section: Methodsmentioning
confidence: 99%
“…In nondiabetic, but not diabetic, ESRD patients receiving chronic hemodialysis therapy, Giordano et al [218] reported a marked improvement in HRV, which correlated negatively with uremia. Mylonopoulou et al [219], in contrast, observed enhanced HRV parameters in both diabetic and nondiabetic ESRD patients, but the effect was more pronounced in the nondiabetic population. Conversion from conventional to nocturnal hemodialysis, which allows more efficient removal of uremic toxins, was associated with improved BRS, increased HF (vagal) power of HRV, and a normalized LF/HF ratio of HRV [101,220].…”
Section: Renal Replacement Therapymentioning
confidence: 85%
“…One of the serious consequences of CKD in the cardiovascular system is impairment in the autonomic cardiovascular control, which is reflected in the depressed HRV. Although, hemodialysis procedure ameliorate clinical outcomes and survival in uremic patients, chronic exposure to hemodialysis seems to induce changes in HRV [94]. In addition autonomic neuropathy induce alterations in HRV and there is evidence that high fluid overload met in hemodialysis patients also impairs ANS activity, leads to hypertension and left ventricular hyperthrophy where enhances cardiac mortality [95].…”
Section: Discussion-conclusionmentioning
confidence: 99%